ARTIFICIAL INTELLIGENCE IMPLEMENTATION OF RESTFULL WEB SERVICE IN LANGUAGE TRANSLATION USING MOSES DECODER METHOD FOR ANDROID APPLICATIONS - Saekoni, Ahmad; Ipnuwati, Sri (YHMM PUBLISHING, 2023)
Language is the ability that humans have to communicate with other humans using signs, such as words and gestures. Estimates of the number of languages in the world vary between 6,000–7,000 languages. However, precise approximations depend on an arbitrary change that may occur between languages and dialects. Natural languages are speech or sign languages, but any language can be encoded into a second medium using audio, visual, or tactile stimuli, for example, graphic writing, braille, or whistles. This is because human language is independent of modality. With so many languages, it results in a lack of understanding of other languages, for example, if we meet someone who speaks a different language from us, we don't understand what that person is reading. With this the author wants to create an Artificial Intelligence System to assist in translating each language into other languages.